"THE GRIMASES OF THE REAL" IN JACQUES LACAN'S PSYCHOANALYSIS - Audronė Žukauskaitė (Problemos)
J. Lacan's theory of psychoanalysis is based on the ternary structure of the Real, the Imaginary, and the Symbolic. The phenomenons of dream, phantasy, and trauma illustrate how these three dimentions are interwoven: phantasy and dream are imaginary constructions which open the Real of desire; trauma is usually considered as a "real event", but its meaning is constituted only as the effect of imaginary and symbolic articulations. This means that the field of psychoanalysis is of discoursive nature: it has the non-necessary and anti-essential character and is always open to future interpretations. These theorethical presuppositions signify that you can never see the face of reality; what is accessible to our apprehension are "the grimaces of the Real".